Benefit-finding experiences of liver transplant recipients who underwent perioperative extracorporeal membrane oxygenation treatment: a qualitative research - Lei, Zhiying; Mo, Yuanyuan; Huang, Huiqiao; Huang, Lina; Zhou, Jiehui; Dong, Jianhui; Zeng, Juhua; Liu, Lu; Sun, Xuyong (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to examine the benefit-finding experiences of liver transplant recipients who undergo perioperative extracorporeal membrane oxygenation (ECMO) treatments in order to provide targeted nursing care and promote mental health among these patients.MethodsThis study employed the phenomenological research approach within the framework of qualitative research. The determination of the sample size was predicated on achieving information saturation. Between June 2023 and March 2024, eight liver transplant recipients who underwent perioperative ECMO treatment at a qualified liver transplantation hospital in Guangxi were purposively selected for semi-structured interviews. In line with the cognitive adaptation theory, this study employed template analysis as the analytical approach, wherein each word in the text content was meticulously examined and categorized into their respective structures based on the theory's three frameworks. Throughout the analysis process, the researchers continuously refined and adjusted abstract content placed within templates while exploring the potential emergence of new themes.ResultsThe study involved a total of eight participants, comprising seven male and one female patient, aged between 43 and 68 years. Among the eight patients, seven had grade 3 or higher coronary artery disease, and one had severe arrhythmia, all of which were attributed to heart conditions necessitating ECMO support during liver transplantation. The ECMO types used were exclusively VA, with auxiliary durations varying between 5 h and 9.5 h. Three overarching themes and seven corresponding sub-themes were extracted: (1) the search for meaning, including a strong desire to survive, recognize the meaning of therapy; (2) gaining a sense of mastery, including a sense of control over one's body and psychological; (3) self-enhancement, including perceiving social support, strengthening self-management, and affirming self-worth.ConclusionsLiver transplant recipients who undergo preoperative ECMO treatment can have benefit-finding experiences. This study indicates that medical professionals should not only focus on timely and accurate treatment but also prioritize addressing patients' psychological needs while caring for critically ill individuals. Clinical medical staff can guide patients in engaging in positive psychological construction, exploring and providing effective social support resources, fostering patients' self-health management, and enhancing the level and patients' ability of benefit-finding by strengthening knowledge, education, and establishing psychological mutual assistance platforms after liver transplantation.